PROSUMER BEHAVIOR OF THE ARMY FANDOM OF BTS IN INDONESIA AS A FORM OF NEW CONSUMERIST SOCIETY - Nanda, Larassatti Dharma; Tjahjani, Joesana (UI Scholars Hub, 2024)
One of the most influential K-pop groups in the world is Bangtan Sonyeondan, abbreviated as BTS. BTS' success can also be determined by their extensive community of fans who create a fandom culture worldwide, including in Indonesia. This paper investigates the BTS fandom consumerism behavior, which is called ARMY, and its relation to Indonesia's participatory fan culture. This research focuses on how BTS's managing company creates a fandom image and how Indonesian fans react. This article is qualitative research using a literature review as the method. Analysis of this paper uses the consumerist society theory by Jean Baudrillard (1986) to explain how the company creates simulacra and hyperreality of BTS as their marketing strategy. Another theory is Jenkins (2012), which states that a prosumer fan culture is used to analyze the fan's resistance to consumerism from the fandom's point of view. This article has several main findings. Big Hit Entertainment uses the creation of hyperreality to make BTS engage with the fans and stimulate consumption. Indonesian fans are doing presumption as a resistance to being submissive customers of Big Hit Entertainment, but in the end, helping it opens a new potential market.